European Novel Foods Policy at a critical juncture: drawing lessons for future Novel Food Governance through a retrospective examination of Regulation 258/97 - Hyde, Richard; Hartley, Sarah; Millar, Kate (Food and Drug Law Institute, 2017)
This paper presents a timely analysis of the European Union (EU) Novel Foods Regulation EC 258/97, identifying trends in the policy process and the applications that have been made under the regulation. The ways that the Novel Foods Regulation has functioned to govern new foods placed on the European market is considered, and a number of important trends are described. A historical account of EU policy regarding novel foods is presented, including an analysis of the changes to Novel Foods Regulation and an analysis of data drawn from the European Commission’s own records of novel foods applications is conducted. The ways Novel Foods Regulation has functioned to govern new foods placed on the European market is revealed. A number of important trends in full applications are explored, along with substantial equivalence applications and unapproved foods that are placed on the market. This data is used to analyze the empirical legitimacy of the recent amendments to EU novel foods governance which will come into force in 2018, suggesting that change was needed, and supports the centralizing approach taken by the Commission. However, the analysis identifies potential risks and uncertainties in recent amendments to EU novel foods governance and considers the challenges of Brexit to the novel foods regime.